Challenges to Identity Integration Indirectly Link Experiences of Heterosexist and Racist Discrimination to Lower Waking Salivary Cortisol in Sexually Diverse Latinx Emerging Adults - Parra, Luis Armando; Hastings, Paul David (Frontiers in Psychology, 2020)
Heterosexist and racist discrimination may adversely impact neurobiological processes implicated in the physical and psychosocial well-being of sexually diverse Latinx people. Yet, little is known about how experiences of both heterosexist and racist discrimination are associated with adrenocortical and psychological functioning in groups of people with multiply marginalized social group identities. Through the application of the intersectionality, minority stress, and allostatic load frameworks, it was hypothesized that experiences of heterosexist and racist discrimination would be associated with disruptions to diurnal salivary cortisol patterns and challenges to identity integration. A group of sexually diverse (self-identified lesbian, gay, bisexual, and queer) Latinx emerging adults (N = 51; ages 18-29, M = 24.06 years; SD = 2.73) provided saliva samples and completed a series of questionnaires during a four-day testing protocol. Heterosexist and racist discrimination were both positively associated with challenges to identity integration. Challenges to identity integration, in turn, were associated with lower intercepts of diurnal cortisol slopes, and heterosexist and racist discrimination were indirectly associated with lower cortisol intercepts via challenges to identity integration. These findings suggest that experiences of heterosexist and racist discrimination may interconnect by challenging sexual and ethnic/racial identity integration and disrupting adaptive adrenocortical regulation among sexually diverse Latinx emerging adults.